A crucial role of the PD-1H coinhibitory receptor in suppressing experimental asthma. Issue 9 (September 2018) - Liu, Huafeng; Li, Xin; Hu, Li; Zhu, Min; He, Bailin; Luo, Liqun; Chen, Lieping
Abstract Programmed death one homolog (PD-1H) is a cell surface molecule of the B7/CD28 immune modulatory gene family. Although PD-1H has been shown to function as a coinhibitory receptor on T cells to limit naive T-cell activation and proliferation, its role in the regulation of the T-cell response to allergens is unknown. We report here that genetic ablation or blockade of PD-1H drastically promotes pulmonary inflammation with massive accumulation of eosinophils in a mouse model of experimental asthma, indicating a suppressive function of PD-1H in allergic inflammation. The loss of PD-1H led to elevated production of both innate cytokines (IL-6, MCP-1 and TNFα) and Th2 cytokines (IL-5 and IL-13) in the lung, indicating a critical role of PD-1H in suppressing the production of airway inflammatory cytokines. In addition, the loss of PD-1H also impaired the expansion of systemic and pulmonary regulatory T cells during asthma induction. These findings support a critical role of intrinsic PD-1H in the regulation of inflammatory responses to allergens. Finally, we showed that treatment with a PD-1H agonistic monoclonal antibody reduced the severity of asthma, which was accompanied by suppressed lung inflammation. Our findings support PD-1H as a potential target and suggest a possible strategy for the treatment of allergic asthma in humans.